2021
DOI: 10.1126/sciadv.abj2836
|View full text |Cite
|
Sign up to set email alerts
|

Precision communication: Physicians’ linguistic adaptation to patients’ health literacy

Abstract: Physicians’ ability to match their language complexity to patient health literacy increases understanding and reduces disparities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 66 publications
(108 reference statements)
1
13
0
1
Order By: Relevance
“…It is therefore necessary to calibrate choices according to the relationship one wants to establish with the reader. Therefore, linguistic matching or tailoring (Schillinger et al, 2021 , p. 6) is a form of discursive ergonomics.…”
Section: Discussion: Text Simplification and ...mentioning
confidence: 99%
“…It is therefore necessary to calibrate choices according to the relationship one wants to establish with the reader. Therefore, linguistic matching or tailoring (Schillinger et al, 2021 , p. 6) is a form of discursive ergonomics.…”
Section: Discussion: Text Simplification and ...mentioning
confidence: 99%
“…Previous studies [11,12] proved that message tailoring strategies associate with different levels of health literacy in patients. In reference [11], customized HMIs had better self-management outcomes for type 2 diabetes management, such as physical activity, quality of life, and diabetes knowledge.…”
Section: Message Tailoring For Health Literacy Associated With Indivi...mentioning
confidence: 99%
“…In reference [11], customized HMIs had better self-management outcomes for type 2 diabetes management, such as physical activity, quality of life, and diabetes knowledge. Besides, [12] emphasized the importance of mutual understanding between health providers and patients as they tested the effectiveness of tailored/universal language use for patients with high/low health literacy. The result showed that low health literacy patients had a better understanding when physicians interacted with tailored languages.…”
Section: Message Tailoring For Health Literacy Associated With Indivi...mentioning
confidence: 99%
“…The American Diabetes Association (ADA) Standards of Care state that clinicians and diabetes care/education specialists should provide easy-to-understand information and reduce unnecessary complexity when developing care plans in collaboration with people with diabetes [ 44 ]. It is important to note, however, that matching the complexity of language used to a person’s health literacy is associated with better understanding than the use of oversimplified language [ 45 ]. People benefit greatly from acknowledgment of their emotional needs as well as clear explanation of the goals of therapy and how treatments work, using language tailored to their level of health literacy.…”
Section: Initial Assessment Of the Patient’s Needs And Expectationsmentioning
confidence: 99%